The Professionalism of History Teachers in Implementation 2013 Curriculum at SMA Negeri 1 Salatiga - Andani, Ferria; Atmaja, Hamdan Tri; Ba'in, Ba'in (Universitas Negeri Semarang, 2019)
This study aimed to describe the professionalism of history teachers, their perceptions of Curriculum 2013, and their professionalism in implementing Curriculum 2013 at SMA Negeri 1 Salatiga. Utilizing a qualitative descriptive method, data were collected through in-depth interviews, observations, and documentation to provide a comprehensive understanding of the teachers' experiences and practices. The findings indicate that history teachers have effectively adopted a scientific approach in implementing Curriculum 2013, guiding learners through observing, questioning, collecting data, analyzing, and communicating (5M). Teachers no longer face significant challenges in assessing the effectiveness of this approach. The implementation of Curriculum 2013 in teaching history has been thorough, encompassing planning, process, and evaluation stages, with teachers independently creating Learning Implementation Plans (RPPs). This professionalism has led to the efficient execution of the Specialization History Mandatory component, demonstrating teachers' competence in managing all aspects of the curriculum. Overall, the study highlights the successful adaptation and implementation of Curriculum 2013 by history teachers at SMA Negeri 1 Salatiga, reflecting their professionalism and commitment to enhancing the educational experience.